Preparation, Mechanical Properties, and Biocompatibility of Graphene Oxide-Reinforced Chitin Monofilament Absorbable Surgical Sutures - Wei Zhang; Bin Yin; Yu Xin; Lei Li; Guanlin Ye; Junxian Wang; Jianfei Shen; Xiao Cui; Qihui Yang (Marine Drugs, 2019)
Chitin (CT) is a good material to prepare surgical sutures due to its conspicuous biological characteristics. However, the poor mechanical strength of pure CT sutures limits its application. In order to improve its strength, a composite monofilament absorbable suture was prepared in this study using graphene oxide and chitin (GO-CT) using a green method. FT-IR spectra showed that GO-CT contained the characteristic functional groups of GO and CT, indicating that a GO-CT suture was successfully obtained. With the addition of a small amount of GO (1.6wt% solution) in chitin, the breaking tensile strength, knot strength, and knot-pull strength of the GO-CT suture were significantly improved compared to the CT suture. The biocompatibility of the GO-CT suture in vitro was checked by tetrazolium-based colorimetric assays and no cytotoxicity to L929 cells was found. In vivo, the subcutaneous implantation of GO-CT sutures in the dorsal skin of rats found no abnormalities by hematoxylin-eosin staining. Furthermore, there were no significant changes in the gene expression of the inflammatory mediators, interleukin 1β (IL-1β), tumor necrosis factor-α, IL-6, IL-17A, interferon-γ, or IL-10; however, the expression of transforming growth factor β was significantly increased in the first week. In summary, GO-CT sutures may have potential as a suture material in the clinic.